Effect of electrolyte (NaCl) and temperature on the mechanism of cetyl trimethylammonium bromide micelles - Haq, Zia Ul; Rehman, Noor; Ali, Farman; Khan, Nasir Mehmood; Ullah, Hidayat (Penerbit Universiti Kebangsaan Malaysia, 2017)
In the last few decades, surfactants and electrolyte interaction has gained considerable attention of researchers due to their industrial and domestic applications. In this work, the effects of electrolyte (NaCl) on the critical micelle concentration (CMC) of the cationic surfactant cetyltrymethyl ammonium bromide (CTAB) at different temperatures were investigated through different techniques such as conductometry, surface tensiometer and viscosimeter. The results showed that the values of CMC of CTAB decreased with the increase in temperature as well as with the addition of NaCl. The value of CMC for pure CTAB was calculated 0.98M at 303K, which was observed to decrease as temperature increased and got value of 0.95M at 318K. Moreover the addition of electrolyte NaCl into the surfactant lead to lowering of the CMC and obtained value of 0.90M at 3M of NaCl, indicating significant electrostatic interactions between surfactant and electrolyte. Moreover the degree of ionization(α) calculated for pure cationic surfactant CTAB was 0.219, which tends to increase with the addition of electrolyte, while that of counter ion binding values (β) was observed to decrease from 0.780 to 0.201. Furthermore, the conductivity of charged micelle of surfactant and free ions of electrolyte contributed to electric conductivity of aqueous micellar solution of surfactant. The results can be helpful to develop better understanding about interaction between electrolyte and surfactant.